G41 Working with parents and health-care professionals to design, develop and pre-pilot the parent learning needs and preferences assessment tool: the plant study. (27th April 2015) - Swallow, VM; Mightingale, R; Sinha, M
Abstract : Aims: The purpose of the paper is to present a recently completed, multicentred project, the Parent Learning Needs and Preferences Assessment Tool (PLAnT) study, in which we designed, developed and pre-piloted a tool to promote a standardised, multi-disciplinary approach to assessing parents' learning needs/preferences. Health-care professionals spend considerable time teaching parents to safely manage their child's long-term condition/s at home. However, previous research that explored the ways professionals teach parents, and the ways parents learn to manage their child's condition, identified a need for a robust method of assessing parents' learning needs as professionals can find it challenging to individualise parents' skill and knowledge development. Methods: Phase 1: Data from qualitative interviews with 10 parents and 13 multi-disciplinary team professionals from 11 British children's kidney units about their learning/teaching experiences were used to develop the PLAnT. Participants were then asked to comment on the PLAnT via qualitative interviews or an online survey. Phase 2: Thirteen parents were each then paired with one of nine professionals to test the PLAnT; feedback on the experience of administering and completing the PLAnT was then sought from these 22 participants via qualitative interviews. Data were analysed using Framework Analysis. Results: This presentation will explore and discuss development of the PLAnT, and the three key themes that emerged from phase 2 as we piloted it with professionals and parents. Purpose : Why ask parents' about their learning needs/preferences? To gain feedback on professionals teaching or identify prospective needs? Process: What is the best way of identifying parents' learning needs/preferences? Using a structured questionnaire or a semi-structured discussion? Outcome : How can information about parents' learning needs/preferences be used? Are professionals able and willing to adjust their practice to meet parents' needs? Conclusions: Though professionals may develop an understanding of how to support parents' learning over time, they can sometimes misjudge parents' needs. Therefore, parents should routinely be asked about their learning needs/preferences. The PLAnT could be used to identify these needs, though further refinement, piloting and feasibility testing is required in future research to address the questions raised by the current study.